Mechanisms of failure and survival of total femoral endoprosthetic replacements. (May 2019) - Medellin, M. R.; Fujiwara, T.; Clark, R.; Stevenson, J. D.; Parry, M.; Jeys, L.
Abstract : Aims: The aim of this study was to evaluate the prosthesis characteristics and associated conditions that may modify the survival of total femoral endoprosthetic replacements (TFEPR). Patients and Methods: In all, 81 patients treated with TFEPR from 1976 to 2017 were retrospectively evaluated and failures were categorized according to the Henderson classification. There were 38 female patients (47%) and 43 male patients (53%) with a mean age at diagnosis of 43 years (12 to 86). The mean follow-up time was 10.3 years (0 to 31.7). A survival analysis was performed followed by univariate and multivariate Cox regression to identify independent implant survival factors. Results: The revision-free survival of the implant was 71% at five years and 63.3% at ten years. Three prostheses reached 15 years without revision. The mean Musculoskeletal Tumor Society score in the group was 26 (23 to 28). The mechanisms of failure were infection in 18%, structural failures in 6%, tumour progression in 5%, aseptic loosening in 2%, and soft-tissue failures in 1%. Prostheses used for primary reconstruction after oncological resections had lower infection rates than revision implants (8% vs 25%; p = 0.001). The rates of infection in silver-coated and non-silver-coated prosthesis were similar (17.4% vs 19.%; p = 0.869). The incidence of hip dislocation was 10%. Rotating hinge prosthesis had a lower failure rate than fixed hinge prosthesis (5.3% vs 11%). After Cox regression, the independent factors associated with failures were the history of previous operations (hazard ratio (HR) 3.7; p = 0.041), and the associated arthroplasty of the proximal tibia (HR 3.8; p = 0.034). At last follow-up, 11 patients (13%) required amputation. Conclusion: TFEPR offers a reliable reconstruction option for massive bone loss of the femur, with a good survival when the prosthesis is used as a primary implant. The use of a rotating hinge at the knee and dual mobility bearing at the hip may be adequate to reduce the risk of mechanical and soft-tissue failures. Infection remains the main concern and there is insufficient evidence to support the routine use of silver-coated endoprosthesis. Cite this article: Bone Joint J 2019;101-B:522–528.